2018
DOI: 10.1063/1.5023620
|View full text |Cite
|
Sign up to set email alerts
|

Stabilities of protonated water-ammonia clusters

Abstract: Branching ratios of water and ammonia evaporation have been measured for spontaneous evaporation from protonated mixed clusters H(HO)(NH) in the size range 0 ≤ n ≤ 11 and 0 ≤ m ≤ 7. Mixed clusters evaporate water except for clusters containing six or more ammonia molecules, indicating the formation of a stable core of one ammonium ion surrounded by four ammonia molecules and a second shell consisting predominantly of water. We relate evaporative branching ratios to free energy differences between the products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Ammonia loss was also observed in ref. 15 for the pure protium species studied there, likewise at the level of 1%, but ammonia loss fractions were seen for larger clusters. The channel was also seen in ref.…”
Section: Results and Analysismentioning
confidence: 72%
See 3 more Smart Citations
“…Ammonia loss was also observed in ref. 15 for the pure protium species studied there, likewise at the level of 1%, but ammonia loss fractions were seen for larger clusters. The channel was also seen in ref.…”
Section: Results and Analysismentioning
confidence: 72%
“…It has been used previously in ref. [15][16][17][18] and is well tested. The positively charged clusters were produced in a corona discharge source (position (A) in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They further suggested that the difference in the hydrogen-bonded structural arrangement is responsible for the variable dipole moments of anionic and neutral clusters. There are many similar studies on anionic and protonated ammonia-water clusters [56][57][58][59][60][61][62] however, the discussion is avoided for brevity. A large number of studies have been carried out on the structural properties of water clusters using various theoretical as well as experimental methods.…”
Section: Introductionmentioning
confidence: 99%